2021
DOI: 10.1021/acs.jmedchem.1c00124
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2,2-Dimethylbutanoic Acid (HST5040), a Clinical Development Candidate for the Treatment of Propionic Acidemia and Methylmalonic Acidemia

Abstract: Propionic acidemia (PA) and methylmalonic acidemia (MMA) are rare autosomal recessive disorders of propionyl-CoA (P-CoA) catabolism, caused by a deficiency in the enzymes P-CoA carboxylase and methylmalonyl-CoA (M-CoA) mutase, respectively. PA and MMA are classified as intoxication-type inborn errors of metabolism because the intramitochondrial accumulation of P-CoA, M-CoA, and other metabolites results in secondary inhibition of multiple pathways of intermediary metabolism, leading to organ dysfunction and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Alternatively, using primary hepatocyte disease models, a group of scientists from HemoShear Therapeutics have shown that supplementation with disodium citrate partially rebalances the concentration of TCA cycle intermediates [ 138 ], while supplementation with a short-chain carboxylic acid (2,2-dimethylbutanoic acid) is able to reduce intracellular concentrations of metabolites related to propionyl-CoA and methylmalonyl-CoA [ 155 , 156 ]. This latter molecule is now part of a therapeutic clinical trial (NCT04732429) for MMA.…”
Section: Cell and Animal-based Disease Models Of Mmamentioning
confidence: 99%
“…Alternatively, using primary hepatocyte disease models, a group of scientists from HemoShear Therapeutics have shown that supplementation with disodium citrate partially rebalances the concentration of TCA cycle intermediates [ 138 ], while supplementation with a short-chain carboxylic acid (2,2-dimethylbutanoic acid) is able to reduce intracellular concentrations of metabolites related to propionyl-CoA and methylmalonyl-CoA [ 155 , 156 ]. This latter molecule is now part of a therapeutic clinical trial (NCT04732429) for MMA.…”
Section: Cell and Animal-based Disease Models Of Mmamentioning
confidence: 99%
“…PA patients have impaired neurocognitive development, 72 and as a small molecule that penetrates the brain, BBP‐671 has the potential to correct CoASH sequestration and defective TCA cycles in the brain and other affected tissues. Another small molecule approach to PA is treatment with 2,2‐dimethylbutyrate (HST5040), which enters cells and is converted to its CoA thioester derivative 38,39 . This treatment reduces C3‐CoA and its downstream metabolites by sequestering CoASH as the HST5040 thioester.…”
Section: Discussionmentioning
confidence: 99%
“…Another small molecule approach to PA is treatment with 2,2‐dimethylbutyrate (HST5040), which enters cells and is converted to its CoA thioester derivative. 38 , 39 This treatment reduces C3‐CoA and its downstream metabolites by sequestering CoASH as the HST5040 thioester. However, there are animal toxicities that arise from exposure to xenobiotic carboxylic acids, notably valproic acid, that are directly attributed to CoASH sequestration into non‐metabolizable thioesters, 62 , 73 , 74 , 75 , 76 , 77 and the utility of HST5040 remains to be tested in a PA mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations